2001
DOI: 10.1002/1096-8628(2001)9999:9999<::aid-ajmg1144>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Glucocerebrosidase mutations among African-American patients with type 1 Gaucher disease

Abstract: While the inherited deficiency of the enzyme glucocerebrosidase (Gaucher disease) is panethnic in its distribution, there have not been studies of the mutations encountered in specific ethnic groups in the United States, other than those on Ashkenazi Jews. We present the clinical descriptions and genotypes of seven patients of African-American ancestry with type 1 Gaucher disease, and summarize the published literature regarding the genotypes encountered in this population. All seven of the patients had modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 34 publications
1
11
1
2
Order By: Relevance
“…Lysosomal disorders such as metachromatic leukodystrophy (MLD) [30], Krabbe disease [31] and Gaucher disease [32] all have accumulation of cerebroside sulfate that appears to cause myelination defects in nerve system as well as hepatomegaly. We also see accumulation of cerebroside sulfate in radial glia and hepatocytes in dxa mutant larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Lysosomal disorders such as metachromatic leukodystrophy (MLD) [30], Krabbe disease [31] and Gaucher disease [32] all have accumulation of cerebroside sulfate that appears to cause myelination defects in nerve system as well as hepatomegaly. We also see accumulation of cerebroside sulfate in radial glia and hepatocytes in dxa mutant larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical reports (Table 1) Case 1, a 37-year-old African-American male with Gaucher's disease type 1, was diagnosed at age 15. This case may have been reported previously (23). He has been followed at Cincinnati Children's Hospital Medical Center every 6-12 months for the past 10 years.…”
Section: Methodsmentioning
confidence: 83%
“…The g.2600‐2602delTAC allele could be derived from a reported patient, but in the absence of detailed clinical information this is difficult to ascertain (10, 23). Even if this is the case, more extensive clinical information and sequence data are reported here.…”
Section: Discussionmentioning
confidence: 99%
“…Lysosomal storage diseases are hereditary diseases of humans and other mammalian species characterized by intracellular accumulation of macromolecular substrates caused by deficiency of lysosomal hydrolases. Many different types of lysosomal storage diseases, in which specific substrates are accumulated in tissues have been reported in humans (Bennet et al 1995;Hahn et al 1997;Park et al 2001;Groener et al 2003) and various mutations in the genes encoding these enzymes have been found in patients of these diseases (Myerowitz 1997;Nilssen et al 1997;Park et al 2001;Groener et al 2003). Similar lysosomal storage diseases have been reported in domestic animals, including cattle, sheep, cats, and dogs (Donnelly & Sheahan 1977;Ryder & Simmons 2001;Kanae et al 2007).…”
Section: Introductionmentioning
confidence: 82%
“…2003) and various mutations in the genes encoding these enzymes have been found in patients of these diseases (Myerowitz 1997; Nilssen et al. 1997; Park et al. 2001; Groener et al.…”
Section: Introductionmentioning
confidence: 99%